Pintura Fresca Vol.18 No.59 (Cultura de Paz, 2013)
Lucía MartínezTito ChamorroSuyen TorresEdgar PasquierDOI: http://dx.doi.org/10.5377/cultura.v18i59.1054Cultura de Paz • Año XVIII • N° 59 • Enero - Abril 2012